Deepening Financial Markets in Francophone West Africa - Paul Collier (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
The financial sector is becoming more important because of the natural resource booms. The taxation of natural resource exports will generate large increases in revenues and this will transform the ability of governments to borrow in the markets for sovereign debt. These constitute temporary influxes of money : resources will deplete and debt must be serviced. Hence, to be sustainable, they must be channelled into productive assets. The public financial sector – central banks, sovereign asset funds, and development banks – has the critical role of administering this process.
Keywords: F15; 330